Localization of nicotinic acetylcholine receptor alpha-subunit transcripts during myogenesis and motor endplate development in the chick (The Rockefeller University Press, 1989)
In 15-d-old chick latissimi dorsi muscles, the nicotinic acetylcholine receptor (AChR) alpha-subunit mRNA is densely accumulated at the level of subsynaptic nuclei of the motor endplate (Fontaine et al., 1988). In this paper, using in situ hybridization with genomic probes, we further show that the expression of the AChR alpha-subunit gene in the embryo, revealed by the accumulation of mature mRNAs, starts in myotomal cells and persists during the first stages of muscle development in a majority of muscle nuclei. Subsequently, the distribution of AChR alpha- subunit mRNAs becomes restricted to the newly formed motor endplates as neuromuscular junctions develop. To assess the transcriptional activity of individual nuclei in developing muscles, a strictly intronic fragment of the AChR alpha-subunit gene was used to probe in situ the level of unspliced transcripts. AChR alpha-subunit unspliced transcripts accumulate around a large number of sarcoplasmic nuclei at embryonic day 11, but can no longer be detected at their level after embryonic day 16 in the embryo. A similar decrease in the accumulation of AChR alpha-subunit transcripts is observed between day 4 and day 6 in primary cultures of muscle cells. On the other hand, in vivo denervation and in vitro blocking of muscle electrical activity by the sodium channel blocker tetrodotoxin results in an increase in the labeling of muscle nuclei. Yet, only 6% of the muscle nuclei appear labeled by the strictly intronic probes after denervation. The possible significance of such heterogeneity of muscle nuclei during motor endplate formation in AChR gene expression is discussed.